2019
DOI: 10.3390/atmos10070378
|View full text |Cite
|
Sign up to set email alerts
|

Weather Based Strawberry Yield Forecasts at Field Scale Using Statistical and Machine Learning Models

Abstract: Strawberry is a high value and labor-intensive specialty crop in California. The three major fruit production areas on the Central Coast complement each other in producing fruits almost throughout the year. Forecasting strawberry yield with some lead time can help growers plan for required and often limited human resources and aid in making strategic business decisions. The objectives of this paper were to investigate the correlation among various weather parameters related with strawberry yield at the field l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…The result also showed that six VIs worked better than LAI as yield estimators. Maskey et al [113] utilized predictive principal component regression (PPCR), neural network (NN), and random forest (RF) models to forecast strawberry yield using 26 parameters related to leaf and canopy properties, soil characteristics, and weather conditions. Each of the selected weather parameters was highly correlated with strawberry yield, and the neural network (NN) analysis provided the best prediction accuracy (95%).…”
Section: Strawberry Yield Predictionmentioning
confidence: 99%
“…The result also showed that six VIs worked better than LAI as yield estimators. Maskey et al [113] utilized predictive principal component regression (PPCR), neural network (NN), and random forest (RF) models to forecast strawberry yield using 26 parameters related to leaf and canopy properties, soil characteristics, and weather conditions. Each of the selected weather parameters was highly correlated with strawberry yield, and the neural network (NN) analysis provided the best prediction accuracy (95%).…”
Section: Strawberry Yield Predictionmentioning
confidence: 99%
“…Various methods are used for yields prediction like Artificial Neural Networks [6,7], K-Nearest Neighbors [8,4] and Simple Long Short Term Memory Networks (LSTM) [9]. The weather parameters are used as input parameters to predict the yields in [10]; while in [11,5], the corresponding prices to strawberry yields are predicted using various DL compound models like ConvLSTM, CNN-LSTM, CNN-LSTM-GRU with attention along with DL ensemble models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hence, if enough water is available, full irrigation is recommended. Seventh, Maskey and colleagues [8] published a paper exploring the correlation of various environmental factors affecting the yields of strawberries grown in an open field. In addition, they use the principal component regression method, two pattern recognition techniques such as a one-layer neural network model, and the random forest classification method to evaluate yield prediction.…”
Section: Related Workmentioning
confidence: 99%